Socialization and parenting in chinese cultural context - Jo, Pei Tan; Buchanan, Ann; Hanafi, Zahyah (Sekolah Pembangunan Sosial, 2006)
This paper describes the parenting characteristics and behaviour among Chinese families. Specifically it explores some alternative parenting concepts which may be culturally more accurate in describing the non-western parenting behaviour among Chinese parents and children. It outlines key research literature on Chinese parenting in relations to 1) parenting goals and beliefs among Chinese parents and, 2) the notion of Guan and ‘training’ as a parenting dimension in Chinese families. This paper concludes that a further exploration on non-western parenting is warranted for future family research and thus its findings are deemed to be resourceful for multicultural societies.